How does agricultural insurance influence grain production scale? An income-mediated perspective - Dainan Hou; Xin Wang; Xin Wang (Frontiers in Sustainable Food Systems)
IntroductionAgricultural insurance has become a vital instrument in risk diversification, loss compensation, and farmer support, with China emerging as the largest agricultural insurance market globally by premium volume. However, the extent to which agricultural insurance influences grain production scale and the underlying mechanisms remain insufficiently explored.MethodsDifferentiating itself from previous studies, this paper conducts a rigorous theoretical and empirical analysis of how agricultural insurance affects grain planting scale. It further examines the mediating role of farmers’ income in this process, providing novel insights into the complex dynamics between agricultural insurance and production behavior. This study applies the von Neumann-Morgenstern expected utility model, coupled with theories on economies of scale, technology diffusion, and rational choice, to examine the theoretical links between agricultural insurance, farmers’ income, and grain production scale.ResultsUsing panel data from 27 Chinese provinces between 2011 and 2021, analyzed through fixed-effects and mediation models, the study finds that agricultural insurance positively, albeit moderately, impacts the scale of grain production, with farmers’ income serving as a partial mediating factor.DiscussionBased on these findings, we recommend expanding agricultural insurance coverage, developing a multi-level insurance framework, and enhancing insurance protection levels to bolster sustainable agricultural development and food security in China.